Dynamics of Economic Growth in West Sumatra: The Role of Digital Zakat and the Impact of Inflation through Financial Transformation - Aulia, Wahyu; Kamarni, Neng (UIN Sunan Kudus, 2023)
Zakat isa significant source of funding with profound implications for economic growth, particularly in the West Sumatra region. However, there is an opportunityfor improvement sincethe actual collection in theregion falls below optimal standards. In recognizing theproblem, Zakat Forum (FOZ) developsthe idea of Digizakat, known asdigital zakat, to improve itscollection,and changes in the impact of inflation rates on thestability of the economy. Therefore, thisstudy aimed to examine the potential effects of inflation and digitally collected zakat on West Sumatra's economic growth from short-and long-term perspectives. Secondary data from BAZNAS and BPS West Sumatra are used to conduct a thorough analysis ofmonthly digital zakat collection records from 2016 to 2020.To evaluate the impact of zakat digitization on economic growth, Vector Autoregression(VAR) methodis used. The results show that inflation and the digitization of zakat have a negligible short-term impact on regional economic growth. Increased literacy, tighter government oversight, and maintenance of stable inflation rates are necessary to maximize the impact of zakat digitalizationto improve economic growth and public welfare. This showsthe necessity for additional effortsand the development of intricate models to comprehend the variables influencing economic growth, particularly the adjustment ofzakat digitalization to obtaina substantial impact